Narrativas Que Construyen Las Madres Cuyos Hijos Fueron Víctimas De Las Ejecuciones Extrajudiciales, Respecto A Los Tres (3) Actores Armados: Ejército Nacional, Guerrilla Y Paramilitares - Naranjo Lovera, Katherine Edith (Universidad Antonio Nariño, 2024)
The purpose of this research was to know the narratives of mothers, victims of extrajudicial executions with respect to the three armed actors: National Army, Guerrilla and Paramilitaries; before during and after the victimizing event, for this we will work with 3 women victims of this scourge. This research was developed with a narrative design of qualitative type and descriptive scope